Benign fibroushistiocytoma of the gingiva - Palani Rajathi; Mathew Jacob; Indra Priyadharshini; Balakrishnan Sekar (Journal of Pharmacy and Bioallied Sciences, 2013)
Benign fibroushistiocytoma is a benign connective tissue tumor rarely seen affecting the head and neck region. These tumors were believed to be of histiocytic origin as they are comprised of cells, which showed spindled morphology and cells with a round histiocytic appearance. The current concept consents that the lesional cells rather represent a fibroblastic differentiation. Diagnosis of these tumors proves to be challenging even with the use of immunohistochemistry due to lack of any specific markers. Here, we describe a case which presented in the gingiva mimicking a reactive lesion, which in fact was a tumor.